2007
DOI: 10.1186/1471-2105-8-149
|View full text |Cite
|
Sign up to set email alerts
|

Using gene expression data and network topology to detect substantial pathways, clusters and switches during oxygen deprivation of Escherichia coli

Abstract: Background: Biochemical investigations over the last decades have elucidated an increasingly complete image of the cellular metabolism. To derive a systems view for the regulation of the metabolism when cells adapt to environmental changes, whole genome gene expression profiles can be analysed. Moreover, utilising a network topology based on gene relationships may facilitate interpreting this vast amount of information, and extracting significant patterns within the networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
1
6
1
Order By: Relevance
“…They suggest that under aerobic conditions NADH is limiting due to it being oxidized by the NADH oxidase and therefore unavailable for reduction of acetaldehyde to ethanol. These data combined with lower intracellular glucose and ED pathway intermediates (Table 1 ) would agree with such a model and previous reports [ 30 , 31 ]. While we did not obtain the data for NAD + , NADH, ATP metabolites, altered redox balance with concomitant increases in other metabolites produced such as acetate, lactate, acetoin, and acetaldehyde in the presence of oxygen may account for lower ethanol production (Table 1 , Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They suggest that under aerobic conditions NADH is limiting due to it being oxidized by the NADH oxidase and therefore unavailable for reduction of acetaldehyde to ethanol. These data combined with lower intracellular glucose and ED pathway intermediates (Table 1 ) would agree with such a model and previous reports [ 30 , 31 ]. While we did not obtain the data for NAD + , NADH, ATP metabolites, altered redox balance with concomitant increases in other metabolites produced such as acetate, lactate, acetoin, and acetaldehyde in the presence of oxygen may account for lower ethanol production (Table 1 , Fig.…”
Section: Discussionsupporting
confidence: 93%
“…P. aeruginosa OprB transports glucose, mannitol, glycerol, and fructose. The E. coli expression of pathways for hexose uptake and metabolism has been shown to be up-regulated in the response to oxygen deprivation [ 30 ]. A number of ED and pyruvate biosynthetic pathway genes ( gntK, edd, eda, gap ) were showed higher expression levels under anaerobic conditions at 26 h when compared to the equivalent aerobic time point, but at levels not considered significant (see Additional file 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even without novobiocin addition, his operon expression is reduced by high osmolarity or anaerobiosis (169). This experimental result does not support a prediction from a recent metabolic network model that his operon expression should increase during oxygen deprivation (190). Other experiments with mutants lacking the his attenuator region (Δ his01242 ) or defective in ppGpp synthesis ( relA ) indicated that supercoiling control of his operon expression occurs mostly by changes in attenuation rather than by changes in the frequency of transcription initiation from the primary promoter hisp1 (see below).…”
Section: The Histidine Biosynthetic Pathway and Enzymescontrasting
confidence: 93%
“…In valine catabolism, methylmalonate semialdehyde is converted to propionyl-coenzyme A by methylmalonate semialdehyde dehydrogenase (spot 156) [39]. Glycine dehydrogenase (spot 123) is a part of the glycine cleavage system [40], and glycine hydroxymethyltransferase (spots 124 and 125) can inter-convert glycine and serine via methylation or demethylation.…”
Section: Peptides Involved In Amino Acid Metabolism and Secondary Metmentioning
confidence: 99%